2014
DOI: 10.1007/s00022-014-0245-z
|View full text |Cite
|
Sign up to set email alerts
|

On doubly warped product immersions

Abstract: Abstract. In this paper we study fundamental geometric properties of doubly warped product immersion which is an extension of warped product immersion. Moreover, we study geometric inequality for doubly warped products isometrically immersed in arbitrary Riemannian manifolds. Mathematics Subject Classification (2010). 53C40, 53C42, 53B25.Keywords. doubly warped product, doubly warped immersion, totally umbilical submanifold, shape operator, doubly warped product representaion, geometric inequality, eigenfuncti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…Let M µ × λ N be a doubly warped product manifold whose warping functions λ and µ are harmonic functions. Then, there exists no isometric minimal immersion of a doubly warped product M µ × λ N into a Riemannian manifold of negative curvature [32]. (1) Every doubly warped product M µ × λ N does not admit an isometric minimal immersion into any Riemannian manifold of negative curvature.…”
Section: Some Results On Doubly Warped Product Manifoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Let M µ × λ N be a doubly warped product manifold whose warping functions λ and µ are harmonic functions. Then, there exists no isometric minimal immersion of a doubly warped product M µ × λ N into a Riemannian manifold of negative curvature [32]. (1) Every doubly warped product M µ × λ N does not admit an isometric minimal immersion into any Riemannian manifold of negative curvature.…”
Section: Some Results On Doubly Warped Product Manifoldsmentioning
confidence: 99%
“…By setting F (t) = e t and substituting Equations (32) and (33) in (28), it could be concluded that Ψ is F -harmonic.…”
Section: Examplementioning
confidence: 99%
“…In particular, if for example f 2 = 1, then M = M 1 × f1 M 2 is called a (singly) warped product manifold. A singly warped product manifold M 1 × f1 M 2 is said to be trivial if the warping function f 1 is also constant [1,18,21,29,31,36]. It is clear that the submanifolds M 1 × {q} and {p} × M 2 are homothetic to M 1 and M 2 respectively for each p ∈ M 1 and q ∈ M 2 .…”
Section: Preliminariesmentioning
confidence: 99%
“…Let ψ be a smooth function on a Riemannian n-manifold M . Then the Hessian tensor field of ψ is given by (8) and the Laplacian of ψ is given by…”
Section: Preliminariesmentioning
confidence: 99%
“…Doubly warped products can be considered as a generalization of singly warped products which were mainly studied in [15,16]. A. Olteanu [11], S. Sular and C.Özgür [13], K. Matsumoto [9] and M. Faghfouri and A. Majidi in [8] extended some properties of warped product submanifolds and geometric inequalities in warped product manifolds for doubly warped product submanifolds into Riemannian manifolds.…”
Section: Introductionmentioning
confidence: 99%